Analysis of the Influence of Organizational Culture on the Performance of Science Educators in the Military Environment - Nugraha Gumilar; Dekki Widiatmoko (Universitas Syiah Kuala, 2023)
This study aims to analyze the influence of organizational culture on the performance of science educators in the military environment. The study was conducted using a survey method on science educators in various military educational institutions. Data were collected through a questionnaire designed to measure science educators' perceptions of organizational culture and their performance. The analysis method used was linear regression to see the relationship between the independent variable (organizational culture) and the dependent variable (science educator performance). The results of the study showed that organizational culture has a significant influence on the performance of science educators. This finding suggests that a good organizational culture can improve the effectiveness of science educators in carrying out their duties. The application of strong organizational culture values has been shown to increase the motivation and professionalism of science educators, which ultimately has a positive impact on their performance. Values such as discipline, integrity, and cooperation that are upheld in military organizations help create a conducive work environment for the development of science educators. This study makes an important contribution to understanding the factors that influence the performance of science educators in the military environment, as well as providing recommendations for military education managers to strengthen organizational culture in order to improve the quality of education and training.